Effect of different stages of fruit maturity and size grading on seed quality in jatropha (Jatropha curcas) - RAMANADANE, T; NARAYANAN, A L (The Indian Journal of Agricultural Sciences, 2014)
The seed quality of Jatropha harvested at different stages of fruit maturity was evaluated to determine the right stage of harvesting for getting high quality seeds at Karaikal, Puducherry (UT) in the year 2011. One hundred freshly opened flowers were tagged at anthesis in 25 numbers of two year old trees. The fruit set in each tagged flower was recorded for seven weeks, consecutively. The results revealed that, only 59 per cent of the flowers set fruits and four different colour changes in fruits, viz. light green (Stage I), lemon yellow (Stage II), dark brown (Stage III) and dark brown with hairline cracks (Stage IV) were observed during maturation at 21, 28, 42 and 49 days after anthesis (DAA), respectively. Observation on seed germination indicated that the seeds obtained from stage III was on par with stage IV (68 per cent) and excelled stage I (4 per cent) and stage II (56 per cent). Between stages III and IV, the seeds obtained from stage III was found to be superior to stage IV, attributed due to higher vigour index and hence considered as the stage of physiological maturity for Jatropha. The larger sized capsules had excelled medium and smaller sized in terms of both vigour and viability and emphasized the significance of size grading for elite seedling production in Jatropha.